2018
DOI: 10.3390/ma11112136
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Sensitivity Characteristics of SBS/CRP-Modified Bitumen after Different Aging Processes

Abstract: Temperature sensitivity characteristics of bitumen can be evidently influenced by modifier types and natural aging processes. Many types of modifiers have been used to improve the temperature sensitivity performance of bitumen, but their effects are different. Therefore, different bitumen specimens as well as SBS/CRP (Styrene-butadiene-styrene polymer/crumb rubber powder)-modified bitumen were prepared and the temperature sensitivity characteristics of bitumen after different aging processes were analyzed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…However, utilisation of stiffer binders often results in stiff mixes that have workability related issues since they are not easy to place and compact to the desired density. Furthermore, sometimes stiff binders are modified with polymers that further increase their viscosity hence substantially negatively impacting on workability at a given temperature [15,16]. Asphalt mixes with such stiff binders result in insufficient pavement compaction that often lead to significant performance-related defects resulting from high air voids.…”
Section: Binder Selectionmentioning
confidence: 99%
“…However, utilisation of stiffer binders often results in stiff mixes that have workability related issues since they are not easy to place and compact to the desired density. Furthermore, sometimes stiff binders are modified with polymers that further increase their viscosity hence substantially negatively impacting on workability at a given temperature [15,16]. Asphalt mixes with such stiff binders result in insufficient pavement compaction that often lead to significant performance-related defects resulting from high air voids.…”
Section: Binder Selectionmentioning
confidence: 99%
“…He and authors conducted research on SBS/rubber powder-modified asphalt, and the results showed that the flexibility and structure of the SBS/rubber powder composite-modified asphalt after UV aging were not greatly affected. Dynamic shear rheometer (DSR) and bending beam rheometer (BBR) tests showed that the compositemodified asphalt still had excellent temperature sensitivity and low-temperature crack resistance after aging, and the modification of asphalt by SBS and rubber powder was mainly physical modification [13]. Mo and authors performed DSR tests, rutting tests and three-point bending tests and demonstrated that SBS/rubber powder compositemodified asphalt had good performance in both high-and low-temperature environments, and the addition of composite-modified materials improved the rutting resistance and low-temperature crack resistance of asphalt mixtures [14].…”
Section: Introductionmentioning
confidence: 99%
“…C. Loderer et al [29] found that the addition of crumb-rubber to bitumen increases the complex modulus at high temperatures and reduces stiffness at low temperatures. He et al [30] investigated the temperature sensitivity characteristics of bitumen after different aging processes and showed that SBS/CRP(crumb rubber powder)-modified bitumen has a strong anti-aging ability in that its flexibility and structure remain in good condition after long-term aging.…”
Section: Introductionmentioning
confidence: 99%